Fenomena "Mahram Haji" di Indonesia - Najwah, Nurun (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2008)
The  pilgrimage  to  Mecca  is  5th of  Islamic foundation  for  all  the  capable  Moslem  (istitha`ah) without  consideration  of  the  sex  differences  (male  or female).  It`s  a  duty  of  the  women  moslem  are accompanied by mahram. In the one hand, this concept apparently  protect  safety  of  women.  In  the  reality,  in different contect, it represses opportunity of women to act  of  maximal  devotion,  included  the pilgrimage  to Mecca.  So,  this  paper  will  describe  reinterpretation  of term  of  mahram  from  the  text  tradition  of  prophet Mohammed in Indonesian contect.